Metabolomic approach to investigate Dactylis glomerata L. from the VIR collection - N. Yu. Malysheva; T. V. Shelenga; A. E. Solovyeva; T. B. Nagiev; N. V. Kovaleva; L. L. Malyshev (Вавиловский журнал генетики и селекции)
The perennial grass cocksfoot (Dactylis glomerata L.) is a valuable early highly nutritious crop used as green fodder in agricultural production. The species is widespread across the Eurasian continent; it is characterized by plasticity and high ecological and geographical variability. The article considers the metabolic profiles of 15 accessions of the cocksfoot from the collection of the N.I. Vavilov Institute of Plant Genetic Resources (VIR). The material is represented by varieties and wild forms of various origin: the European part of the Russian Federation, Norway and Finland. The study was carried out using gas-liquid chromatography coupled with mass spectrometry. The study and comparison of groups of metabolites of cocksfoot accessions of various ecological and geographical origin was carried out. Statistical processing included the calculation of the main parameters of variability, factor analysis of the correlation system (Qand R-technique), cluster analysis by Ward’s method and discriminant analysis. The variability of the quantitative and qualitative composition of the substances identified was revealed. Based on statistical processing of the results obtained, five groups of cocksfoot accessions were identified, differing in the profile of metabolites. One of the groups with a similar composition of metabolites consisted of accessions from one ecological and geographical region; another, of accessions of different origin. Significant differences were noted in the metabolomic profiles of a late-maturing wild cocksfoot accession from the Republic of Karelia at the booting stage from earlyand mid-maturing accessions at the heading stage; it contained the largest number of free amino acids and the smallest number of identified primary and secondary metabolites. Wild-growing accession k-44020 from Norway surpassed other wild-growing accessions in the content of free amino acids, sugars and phosphates at the heading stage. Wildgrowing accessions differed from breeding varieties with a high content of proline and threonine, indicators of high resistance to lack of moisture and high air temperature.